Diante dos olhos deles: reflexões sobre corpo e contemporaneidade - Souza Júnior, Edilson Brasil de (RATTS, Júnior) (2010)
This work aims to analyze the body potential of the contemporary person in the daily struggle for the conquest of individuality and collective recognition. So, the research is based on the American reality show America's Next Top Model, aiming to understand better, from the experience between the candidates, how tactical and strategic relations are taken between them and the outside world, as well as the body reacts the expectations and consequences originated by these 'everyday encounters' with reality and the Other, turning it into a 'weapon' and in a sociocultural product. Based on this logic, the work aims to analyze how the representations of the female body are designed - imagery and discursively - in the reality show and how the representations when are suited to the exigencies global market of information and consumer goods, reflect social and cultural questions linked to the identity, gender and sexuality in the contemporaneity.